ANALISIS MAKSIMILISASI KEUNTUNGAN DENGAN METODE SIMPLEX DAN PENDEKATAN METODE SOLVER PADA CV .INDOSOTEN - Rezky Hidayat (Institut Sains dan Teknologi Nasional, 2020)
The In the current era of globalization, the economic situation in Indonesia is indeed very concerning. With these conditions, many micro businesses, especially home industry businesses, have to struggle to continue carrying out product activities so that their production businesses develop. CV.Indoshoten is a small-scale company producing four main products, namely onigiri salmon flake, spicy tuna onigiri, salmon mayo onigiri and tuna mayonnaise onigiri. To maintain the continuity and development of production, steps are needed to be able to allocate raw materials and increase profits. Therefore we need an effort to use a method in determining the right combination of use of the production factors of the products made and the combination of the products produced using the linear programming model of maximization problems with the simplex method and for analysis using the solver method. The results of this study that the salmon-filled onigiri product will get a maximum profit of Rp.875,000 if the company produces 125 pieces of salmon flake onigiri and 25 pieces of salmon mayo while the tuna-filled onigiri product will get a maximum profit of Rp.626,692 if the company produces spicy tuna onigiri. 40 pcs and 107 pcs of tuna mayo. If a company has a lot of inputs that must be used for the production process and the main purpose of obtaining profits that can be used is the simplex method, whereas if the user wants to analyze variable changes so that profits remain optimal then use the solver method.